Molecular recognition of DNA double helix : gene regulation and photochemistry of BrU substituted DNA ; development of chemical biology tools /: gene regulation and photochemistry of BrU substituted DNA ; development of chemical biology tools. (2018) - Saha, Abhijit
No abstract available